Asynchronous wood formation in young Acacia mangium planted in Malaysia - Ogata, Yoshiyuki; Nobuchi, Tadashi; Fujita, Minoru; Sahri, Mohammed Hamami (2002)
In general, tropical trees have less-distinct growth rings. Even if the trees have some concentric structures, there is little information on the timing of their formation. The objective of this report is to show the asynchronous wood formation from the observation of indistinct, ring-like structures. Young Acacia mangium planted in Malaysia was investigated for asynchronous wood formation anatomically and macroscopically. Tree heights and girths at breast height for 28 trees were measured every other week. Wood disks from four trees were sampled at breast height for this research. The radial variation of vessel dimensions and the number of cambial cells in different radial directions and the wood anatomy of discontinuous bands were investigated using thin sectioning and soft radiographic methods. The vessel dimension was quite different in their radial variation even for four radial directions with a similar radius. There was a large variation in the number of cambial cells among radial directions in young Acacia mangium. Bands of low density included a layer of vessels aligned in a spiral rather than in a closed circle.